Preparation method of acid-modified encapsulated metal catalyst for improving tar quality
Ni@HZSM-5 was acidified by loading SO42-/ZrO2, and using ammonium sulfate acidification treatment to form Ni@HZSM-5-SZ molecular sieve, which solved the problem of insufficient activation performance of encapsulated metal catalysts, significantly improved the tar cracking performance and Light oil yield avoids damage to the molecular sieve structure.
Patent Information
- Application Number
- CN202411251906.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The existing encapsulated Ni-based catalysts have insufficient activation performance in tar cracking, resulting in poor tar cracking performance, and the use of H2SO4 leads to damage to molecular sieve structure and loss of acidic sites.
Ni@HZSM-5 is acidified by loading SO42-/ZrO2, and ammonium sulfate is used to acidify Ni@HZSM-5-SZ molecular sieve to enhance the acidity of the catalyst, avoid the damage to the molecular sieve structure, and form super acidic sites to improve the Tar cracking performance.
It significantly improves the tar cracking performance, enhances the yield of light components, prevents the damage to the molecular sieve structure, and achieves the improvement of tar quality and the yield of light oil products.
Smart Images

Figure CN119114147A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of energy chemical industry, and in particular to a method for preparing an acid-modified encapsulated metal catalyst for improving tar quality. Background Art
[0002] Since the Ni-based catalyst prepared by the encapsulation method makes the metal Ni mainly participate in the activation of hydrogen-rich gas, except for the acidity of the molecular sieve itself, there are no other active sites involved in the cracking of tar, resulting in insufficient tar cracking performance, so it is necessary to enhance the tar cracking performance.
[0003] Studies have shown that the acid sites in the catalyst play a very important role in the catalytic cracking of tar. They can reduce the activation energy required in the cracking process of tar and promote bond breaking by accepting electron pairs or providing protons H. Solid acid catalysts are widely used in petrochemical and biomass conversion fields as common acid catalysts. Solid acid catalysts can be recycled and reused relative to liquid acids, which is in line with the theme of environmentally friendly development. Among them, sulfated metal oxide catalysts (SO4 2- / M x O y ) is one of the solid acid catalysts, with excellent acid properties and no corrosiveness, and is widely used in the catalytic industry. When the researchers removed silicon by alkali treatment to produce mesopores, they also caused the loss of some acid sites, so they subsequently loaded SO4 2- / ZrO2 (SZ) is used to improve the acidity and acidity of the molecular sieve. Experiments have found that compared with non-catalytic catalysis, the total yield of light components in tar is significantly improved. This is because the super-strong acidic sites formed by SZ increase the cracking of heavy tar components and improve the yield of light components. However, when the proportion of H2SO4 continues to increase, excessive H2SO4 will cause the destruction of the HZSM-5 molecular sieve structure, amorphous deposits will appear and further accumulate on the surface of the molecular sieve and block the pore structure of the molecular sieve, resulting in a large loss of active components and poor tar cracking activity. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing an acid-modified encapsulated metal catalyst for improving the quality of tar, wherein metal zirconium is loaded and acidified with ammonium sulfate to enhance the acidity of the catalyst, thereby improving the tar cracking ability, encapsulating the metal active sites inside the molecular sieve, activating hydrogen-rich gases such as H2 and CH4 generated in the pyrolysis system, thereby generating ·H and ·CH x Small molecular free radicals such as tar pyrolysis fragments can be stabilized to further improve the quality of tar and the yield of light oil products.
[0005] To achieve the above object, the present invention provides a method for preparing an acid-modified encapsulated metal catalyst for improving the quality of tar, by loading SO4 2- / ZrO2 is used to acidify Ni@HZSM-5 to obtain Ni@HZSM-5-SZ molecular sieve, comprising the following steps:
[0006] S1. Preparation of Ni@HZSM-5 molecular sieve;
[0007] S2. Use the Ni@HZSM-5 molecular sieve prepared in S1 to prepare Ni@HZSM-5-SZ molecular sieve.
[0008] Preferably, the specific operation of S1 is:
[0009] S11, put a certain amount of TPAOH, H2O and KH-590 into a beaker, mix and stir for 8 hours, then add a certain amount of Ni(NO3)2·6H2O solution into the mixed solution and stir for 0.5 hours, then slowly add a certain amount of TEOS into the mixed solution and stir for 13 hours;
[0010] S12, prepare a certain amount of TPAOH, H2O, NaOH and Al2(SO4)3·18H2O into a transparent solution, slowly add it dropwise to the mixed solution of S11, and stir in a water bath at 80℃ for 2h;
[0011] S13, after the obtained gel is loaded into an autoclave, it is crystallized in a homogeneous reactor;
[0012] S14, centrifuging the crystallized catalyst to neutrality, drying overnight, and calcining the dried sample in a muffle furnace to obtain a Ni@NaZSM-5 molecular sieve sample;
[0013] S15. Prepare NH4NO3 solution, stir the Ni@NaZSM-5 molecular sieve and NH4NO3 solution in an oil bath, filter and wash, repeat the operation once, dry, and calcine to obtain Ni@HZSM-5 molecular sieve.
[0014] Preferably, the specific operation of S2 is:
[0015] S21, a certain amount of Zr(NO3)2·5H2O was dissolved in deionized water, and then the prepared Ni@HZSM-5 molecular sieve was added to the solution, the mixture was ultrasonicated for 3 h, filtered, washed and dried, and calcined under N2 atmosphere, and the obtained sample was represented as Ni@HZSM-5-Z molecular sieve;
[0016] S22, prepare (NH4)2SO4 solution, mix and stir the sample prepared in S21 with the (NH4)2SO4 solution, then filter and wash until neutral, dry, and then calcine. The obtained catalyst is named Ni@HZSM-5-SZ molecular sieve;
[0017] S23. The obtained Ni@HZSM-5-SZ molecular sieve is calcined at 700°C for 2h under H2 atmosphere, and then the Ni@HZSM-5-SZ molecular sieve is pressed into tablets, crushed and sieved to 20-40 mesh to obtain an acid-modified encapsulated metal catalyst.
[0018] Preferably, the mass fraction of zirconium in the load is 1%, 3%, 5% or 7%.
[0019] Preferably, the crystallization process in S13 is first crystallization at 100° C. for 48 hours and then crystallization at 170° C. for 24 hours.
[0020] Preferably, the temperature for drying overnight in S14 is 100° C., the calcination temperature in the muffle furnace is 550° C., and the calcination time is 5 hours.
[0021] Preferably, the concentration of the NH4NO3 solution in the S15 is 1 mol / L, and the solid-liquid ratio of the Ni@NaZSM-5 molecular sieve and the NH4NO3 solution is 1:15.
[0022] Preferably, the oil bath temperature in S15 is 80° C., the oil bath stirring time is 4 h, the drying temperature is 100° C., the drying time is 12 h, the roasting temperature is 500° C., and the roasting time is 5 h.
[0023] Preferably, the amount of deionized water in S21 is 75 mL, the amount of Ni@HZSM-5 molecular sieve is 5 g, the drying temperature is 80° C., the drying time is 12 h, the calcination temperature is 300° C., and the calcination time is 3 h.
[0024] Preferably, the concentration of the (NH4)2SO4 solution in the S22 is 0.5 mol / L, the solid-liquid ratio of the sample to the (NH4)2SO4 solution is 1:15, the drying temperature is 110°C, the drying time is 12h, the calcination temperature is 600°C, and the calcination time is 5h.
[0025] The present invention loads SZ in different proportions on the basis of Ni@HZSM-5 molecular sieve catalyst to enhance the acidity of the catalyst. Since the use of H2SO4 in the preparation process will destroy the structure of the molecular sieve, ammonium sulfate is used for acidification, thereby creating a catalyst with graded regulation of tar cracking and hydrogen-rich gas activation, and investigating the changing law of tar properties during the in-situ lightening process of tar.
[0026] Therefore, the present invention adopts the above-mentioned method for preparing an acid-modified encapsulated metal catalyst for improving tar quality, which has the following beneficial effects:
[0027] (1) The present invention uses (NH4)2SO4 to acid-modify the Ni@HZSM-5 molecular sieve to prevent the use of H2SO4 from causing damage to the structure of the HZSM-5 molecular sieve.
[0028] (2) Ni@HZSM-5-SZ molecular sieve catalyst prepared by the present invention, SO4 in sulfated zirconium oxide 2- It usually combines with ZrO2 in a coordinated form to form a super acid site.
[0029] (3) The Ni@HZSM-5-SZ molecular sieve catalyst prepared by the present invention and applied to the process of lightening coal pyrolysis tar significantly improves the catalyst acidity and avoids the problem of insufficient tar cracking performance. It is of great significance for the lightening of tar and the improvement of tar quality, and also provides a new way and idea for the directional regulation of substances in the process of lightening tar.
[0030] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is the NH3-TPD curve of different molecular sieve catalysts in the embodiment of the method for preparing an acid-modified encapsulated metal catalyst for improving tar quality of the present invention;
[0032] Figure 2 It is a graph of N2 adsorption-desorption curves of different molecular sieve catalysts in an embodiment of a method for preparing an acid-modified encapsulated metal catalyst for improving tar quality of the present invention. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0034] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0035] Example
[0036] The present invention provides a method for preparing an acid-modified encapsulated metal catalyst for improving the quality of tar, by loading SO4 2- / ZrO2 is used to acidify Ni@HZSM-5 to obtain Ni@HZSM-5-SZ molecular sieve, in which the mass fraction of zirconium in the load is 1%, 3%, 5%, and 7%, which specifically includes the following steps:
[0037] S1. Preparation of Ni@HZSM-5 molecular sieve, the specific operation is as follows:
[0038] S11. Take a certain amount of TPAOH, H2O and KH-590 and put them into a beaker, mix and stir for 8 hours, then add a certain amount of Ni(NO3)2·6H2O solution into the mixed solution and stir for 0.5 hours, then slowly add a certain amount of TEOS into the mixed solution and stir for 13 hours.
[0039] S12. Prepare a transparent solution with a certain amount of TPAOH, H2O, NaOH and Al2(SO4)3·18H2O, slowly add it dropwise to the mixed solution of S11, and stir in a water bath at 80℃ for 2h.
[0040] TPAOH is used as a template for the synthesis of ZSM-5 molecular sieves and plays the role of a pore growth regulator. KH-590 is a silane coupling agent that uses special groups to complex metal ions on the material. Ni(NO3)2·6H2O is the Ni source in the catalyst preparation process, Al2(SO4)3·18H2O is the Al source, providing a metal source for the molecular sieve synthesis process, and TEOS is a silicon source that hydrolyzes under high temperature and pressure to generate SiO2, which forms molecular sieve crystals with other metal sources. NaOH provides an alkaline environment for the synthesis process.
[0041] S13, after the obtained gel is loaded into an autoclave, it is crystallized in a homogeneous reactor at 100° C. for 48 hours, and then crystallized at 170° C. for another 24 hours.
[0042] S14. The catalyst obtained after crystallization was centrifuged to neutrality, dried at 100° C. overnight, and the dried sample was calcined at 550° C. in a muffle furnace for 5 h to obtain a Ni@NaZSM-5 molecular sieve sample.
[0043] S15. Prepare 1 mol / L NH4NO3 solution, stir Ni@NaZSM-5 molecular sieve and NH4NO3 solution in an 80°C oil bath at a solid-liquid ratio of 1:15 for 4 h. After filtration and washing, repeat the operation once, dry at 100°C for 12 h, and calcine at 500°C for 5 h to obtain Ni@HZSM-5 molecular sieve.
[0044] S2. Use the Ni@HZSM-5 molecular sieve prepared above to prepare Ni@HZSM-5-SZ molecular sieve, and the specific operation is as follows:
[0045] S21. Dissolve a certain amount of Zr(NO3)2·5H2O in 75 mL of deionized water, then add 5 g of the prepared Ni@HZSM-5 molecular sieve into the solution, ultrasonicate the mixture for 3 h, filter, wash, dry at 80 °C for 12 h, and calcine at 300 °C for 3 h under N2 atmosphere. The obtained sample is denoted as Ni@HZSM-5-Z molecular sieve.
[0046] S22. Prepare 0.5 mol / L (NH4)2SO4 solution, mix the sample prepared in S21 with the (NH4)2SO4 solution at a solid-liquid ratio of 1:15, then filter and wash until neutral, dry at 110°C for 12h, and then calcine at 600°C for 5h. The obtained catalyst is named Ni@HZSM-5-SZ molecular sieve.
[0047] S23. The obtained Ni@HZSM-5-SZ molecular sieve is calcined at 700°C for 2h under H2 atmosphere, and then the Ni@HZSM-5-SZ molecular sieve is pressed into tablets, crushed and sieved to 20-40 mesh to obtain an acid-modified encapsulated metal catalyst.
[0048] The coal sample in the following embodiment is Xilin Gol coal from Inner Mongolia, and the tar upgrading process is carried out in a stainless steel tube fixed bed reactor with an inner diameter of 14 mm and a length of 290 mm. The reactor is a vertical two-layer structure, and coal, quartz wool, catalyst, and quartz wool are placed in sequence from top to bottom. A gas inlet is provided at the top of the reactor and an outlet is provided at the bottom of the reactor. The liquid product produced by pyrolysis is cooled and collected by N2 into -20°C cold hydrazine, and the light oil content in the oil product is obtained after simulated distillation analysis. The pyrolysis oil yield and light oil yield (dry ash-free basis) are calculated as follows:
[0049]
[0050] Light oil yield = oil product yield × light oil content
[0051] Among them, W 油品 is the mass of oil product; W0 is the mass of coal sample; A ad is the ash content in coal; M ad It is the moisture in the coal.
[0052] Example 1
[0053] Catalyst preparation: 0.235 g of Zr(NO3)2·5H2O was dissolved in 75 mL of deionized water. Then 5 g of the prepared Ni@HZSM-5 molecular sieve catalyst was added to the solution, and the mixture was ultrasonicated for 3 h. After filtering and washing, it was dried at 80 °C for 12 h and calcined at 300 °C for 3 h under N2 atmosphere to obtain Ni@HZSM-5-1Z molecular sieve.
[0054] Prepare a (NH4)2SO4 solution with a concentration of 0.5 mol / L, mix the Ni@HZSM-5-1Z molecular sieve and the (NH4)2SO4 solution at a solid-liquid ratio of 1:15 and stir for 1 hour, then filter and wash until neutral, dry at 110°C for 12 hours, and then calcine at 600°C for 5 hours. The resulting catalyst is named Ni@HZSM-5-1SZ molecular sieve. Calcinate at 550°C in a muffle furnace for 5 hours to obtain Ni@HZSM-5-1SZ molecular sieve; calcine the obtained Ni@HZSM-5-1SZ molecular sieve at 700°C in a H2 atmosphere for 2 hours, press into tablets, crush, and sieve to 20-40 mesh for use.
[0055] The NH3-TPD analysis of the prepared Ni@HZSM-5-SZ molecular sieve is as follows Figure 1 As shown, the N2 adsorption-desorption curve and pore structure are as follows Figure 2 and Table 1.
[0056] Table 1 Structural characteristics of different catalysts
[0057]
[0058] Catalyst performance evaluation: Before the reaction, the catalyst was reduced and activated in a hydrogen atmosphere at 600°C for 1h. The reaction temperature was 600°C, and the flow rate was 300mL / min under N2 atmosphere. The heating furnace reached the specified temperature within 10min and maintained for 30min. The catalyst dosage was 1g and the coal sample was 5g. The experiment was carried out in a fixed bed reactor.
[0059] This is because the loaded solid acid further increases the cracking of tar, and the hydrogen-rich free radicals generated by the hydrogen-rich gas activated by the metal Ni are stabilized in time, which ensures the yield of tar while achieving the lightness of tar, thus achieving the hierarchical regulation of hydrogen-rich gas activation and tar cracking. Figure 1 NH3-TPD analysis of different catalysts showed that after loading SZ, superacidic acid sites were formed, which participated in the tar cracking process.
[0060] Example 2
[0061] Catalyst preparation: Referring to Example 1, the difference between this example and Example 1 is that the Zr content in the Ni@HZSM-5-SZ molecular sieve catalyst is 3 wt.%, expressed as Ni@HZSM-5-3SZ molecular sieve.
[0062] The NH3-TPD analysis of the prepared Ni@HZSM-5-3SZ molecular sieve is as follows Figure 1 As shown, the N2 adsorption-desorption curve and pore structure are as follows Figure 2 and Table 1.
[0063] Catalyst performance evaluation: Experimental conditions refer to Example 1. Figure 1 NH3-TPD analysis of different catalysts shows that this is because as the SZ content of the load increases, the number of super-strong acidic sites also increases further, and the tar cracking performance is further improved.
[0064] Example 3
[0065] Catalyst preparation: Referring to Example 1, the difference between this example and Example 1 is that the Zr content in the Ni@HZSM-5-SZ molecular sieve catalyst is 5 wt.%, expressed as Ni@HZSM-5-5SZ molecular sieve.
[0066] The NH3-TPD analysis of the prepared Ni@HZSM-5-5SZ molecular sieve is as follows Figure 1 As shown, the N2 adsorption-desorption curve and pore structure are as follows Figure 2 and Table 1.
[0067] Catalyst performance evaluation: Experimental conditions refer to Example 1. Figure 1 NH3-TPD analysis of different catalysts shows that the acid sites of Ni@HZSM-5-5SZ molecular sieve are further increased. Figure 2 The N2 adsorption-desorption analysis of different catalysts and the structural characteristics of different catalysts in Table 1 show that when the loading amount is 5SZ, the specific surface area and pore volume of the micropores are 182m 2 / g and 0.07cm 3 / g, the total specific surface area and total pore volume are 344m 2 / g and 0.38cm 3 / g, which is slightly smaller than that of Ni@HZSM-5-3SZ zeolite, indicating that the SZ accumulated on the surface of the zeolite blocks a small part of the pores of the zeolite.
[0068] Example 4
[0069] Catalyst preparation: Referring to Example 1, the difference between this example and Example 1 is that the Zr content in the Ni@HZSM-5-7SZ molecular sieve catalyst is 7 wt.%, denoted as Ni@HZSM-5-7SZ molecular sieve.
[0070] The NH3-TPD analysis of the prepared Ni@HZSM-5-7SZ molecular sieve is as follows Figure 1 As shown, the N2 adsorption-desorption curve and pore structure are as follows Figure 2 and Table 1.
[0071] Catalyst performance evaluation: Experimental conditions refer to Example 1. Figure 1 NH3-TPD analysis of different catalysts shows that Ni@HZSM-5-7SZ molecular sieve has more acidic sites, but Figure 2 The N2 adsorption-desorption analysis of different catalysts and the structural characteristics of different catalysts in Table 2 show that when the loading amount is 7SZ, the specific surface area and pore volume of the micropores decrease to 154m 2 / g and 0.05cm 3 / g, the total specific surface area and total pore volume decreased to 312m 2 / g and 0.34cm 3 / g, indicating that the SZ accumulated on the surface of the molecular sieve blocks the pores of the molecular sieve, affecting the mass transfer during the reaction and easily leading to an accelerated rate of catalyst deactivation due to carbon deposition.
[0072] Comparative Example 1
[0073] Catalyst preparation: 16.5 mL TPAOH, 4.125 mL H2O and 0.125 mL KH-590 were placed in a beaker, mixed and stirred for 8 hours, and then 6.54 mL of 0.1 mol / L nickel nitrate solution was added to the mixed solution and stirred for 0.5 hours. Then 23.12 mL TEOS was slowly added to the mixed solution and stirred for 13 hours; 13.125 mL TPAOH, 6.75 mL water, 0.125 mL NaOH and 1.381 g aluminum sulfate were prepared into a transparent solution, and the prepared transparent solution was slowly added to the previous mixed solution, stirred in an 80 ° C water bath for 2 hours, and then filled into a kettle, crystallized at 100 ° C for 48 hours and 170 ° C for 24 hours in a homogeneous reactor; the obtained catalyst was centrifuged to neutrality, dried at 100 ° C overnight, and then calcined at 550 ° C for 5 hours in a muffle furnace to obtain Ni@NaZSM-5 molecular sieve.
[0074] Prepare 1 mol / L NH4NO3 solution, stir Ni@NaZSM-5 molecular sieve and ammonium nitrate solution at a ratio of 15 mL / g in an 80°C oil bath for 4 h, filter and wash, repeat the operation once, and dry the obtained catalyst at 100°C for 12 h; calcine at 550°C in a muffle furnace for 5 h to obtain Ni@HZSM-5 molecular sieve; calcine the obtained Ni@HZSM-5 molecular sieve at 700°C in a H2 atmosphere for 2 h, press into tablets, crush and sieve to 20-40 mesh for later use.
[0075] The NH3-TPD analysis of the prepared Ni@HZSM-5 molecular sieve is as follows Figure 1 As shown, the N2 adsorption-desorption curve and pore structure are as follows Figure 2 and Table 1.
[0076] Catalyst performance evaluation: Experimental conditions refer to Example 1. Since the loaded SZ forms super acid sites, the tar cracking process is promoted. Figure 1 The corresponding conclusions were obtained by comparing the NH3-TPD analysis of different catalysts, and the reaction results were consistent with the technical solution of the present invention.
[0077] Therefore, the present invention adopts the above-mentioned method for preparing an acid-modified encapsulated metal catalyst for improving tar quality, acid-modifies the encapsulated metal catalyst, creates an acid-modified encapsulated metal catalyst for graded regulation of tar cracking and hydrogen-rich gas activation, and achieves the purpose of improving the tar cracking yield and the yield and content of light oil products. This method solves the problem of insufficient tar cracking performance of encapsulated metal catalysts and low tar yield. It is of great significance to improve the acidity of molecular sieve catalysts, improve tar quality and light tar yield.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing an acid-modified encapsulated metal catalyst for improving tar quality, by loading SO4 2- / ZrO2 is used to acidify Ni@HZSM-5 to obtain Ni@HZSM-5-SZ molecular sieve, which is characterized by: The following steps are involved: S1. Preparation of Ni@HZSM-5 molecular sieve; S2. Use the Ni@HZSM-5 molecular sieve prepared in S1 to prepare Ni@HZSM-5-SZ molecular sieve.
2. The method for preparing an acid-modified encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: The specific operation of S1 is: S11, put a certain amount of TPAOH, H2O and KH-590 into a beaker, mix and stir for 8 hours, then add a certain amount of Ni(NO3)2·6H2O solution into the mixed solution and stir for 0.5 hours, then slowly add a certain amount of TEOS into the mixed solution and stir for 13 hours; S12, prepare a certain amount of TPAOH, H2O, NaOH and Al2(SO4)3·18H2O into a transparent solution, slowly add it dropwise to the mixed solution of S11, and stir in a water bath at 80℃ for 2h; S13, after the obtained gel is loaded into an autoclave, it is crystallized in a homogeneous reactor; S14, centrifuging the catalyst obtained after crystallization to neutrality, drying overnight, and calcining the dried sample in a muffle furnace to obtain a Ni@NaZSM-5 molecular sieve sample; S15. Prepare NH4NO3 solution, stir the Ni@NaZSM-5 molecular sieve and NH4NO3 solution in an oil bath, filter and wash, repeat the operation once, dry, and calcine to obtain Ni@HZSM-5 molecular sieve.
3. The method for preparing an acid-modified encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: The specific operation of S2 is: S21, a certain amount of Zr(NO3)2·5H2O was dissolved in deionized water, and then the prepared Ni@HZSM-5 molecular sieve was added to the solution, the mixture was ultrasonicated for 3 h, filtered, washed and dried, and calcined under N2 atmosphere, and the obtained sample was represented as Ni@HZSM-5-Z molecular sieve; S22, prepare (NH4)2SO4 solution, mix and stir the sample prepared in S21 with the (NH4)2SO4 solution, then filter and wash until neutral, dry, and then calcine. The obtained catalyst is named Ni@HZSM-5-SZ molecular sieve; S23. The obtained Ni@HZSM-5-SZ molecular sieve is calcined at 700°C for 2h under H2 atmosphere, and then the Ni@HZSM-5-SZ molecular sieve is pressed into tablets, crushed and sieved to 20-40 mesh to obtain an acid-modified encapsulated metal catalyst.
4. The method for preparing an acid-modified encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: The mass fraction of zirconium in the load is 1%, 3%, 5% and 7%.
5. The method for preparing an acid-modified encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: The crystallization process in S13 is to first crystallize at 100° C. for 48 hours and then crystallize at 170° C. for 24 hours.
6. The method for preparing an acid-modified encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: The temperature for overnight drying in S14 is 100° C., the calcination temperature in the muffle furnace is 550° C., and the calcination time is 5 hours.
7. The method for preparing an acid-modified encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: The concentration of the NH4NO3 solution in the S15 is 1 mol / L, and the solid-liquid ratio of the Ni@NaZSM-5 molecular sieve and the NH4NO3 solution is 1:
15.
8. The method for preparing an acid-modified encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: The oil bath temperature in S15 is 80° C., the oil bath stirring time is 4 h, the drying temperature is 100° C., the drying time is 12 h, the roasting temperature is 500° C., and the roasting time is 5 h.
9. The method for preparing an acid-modified encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: The amount of deionized water in the S21 is 75 mL, the amount of Ni@HZSM-5 molecular sieve is 5 g, the drying temperature is 80° C., the drying time is 12 h, the calcination temperature is 300° C., and the calcination time is 3 h.
10. The method for preparing an acid-modified encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: The concentration of the (NH4)2SO4 solution in the S22 is 0.5 mol / L, the solid-liquid ratio of the sample to the (NH4)2SO4 solution is 1:15, the drying temperature is 110°C, the drying time is 12h, the calcination temperature is 600°C, and the calcination time is 5h.
Citation Information
Patent Citations
Method for preparing loaded molecular sieve catalyst by using catalytic cracking of biomass gasification tar
CN104549450A
Superacid-coated HZSM-5 molecular sieve catalyst and preparation method and application thereof
CN106076401A
ZSM-5 packaged single atom layer Pd catalyst as well as preparation method and application thereof
CN107983401A
Method for loading sulfated zirconium oxide to HZSM-5 molecular sieve to prepare solid acid catalyst and application
CN108889333A
Method for preparing difunctional composite catalyst of light aromatics from benzene and synthesis gas in one step
CN110116022A
